Magneto-optical imaging characteristics of weld defects under alternating and rotating magnetic field excitation. (15th April 2019) - Gao, Xiangdong; Du, Liangliang; Ma, Nvjie; Zhou, Xiaohu; Wang, Congyi; Gao, Perry P.
Highlights: Magneto-optical imaging method based on rotating magnetic field excitation. Nondestructive testing of surface and subsurface defects. Histogram equalization can improve the contrast of magneto-optical images. Detection effect of cruciform welding seam. Abstract: This paper mainly examines the characteristics of magneto-optical (MO) images of weld defects under alternating and rotating magnetic field excitation. Weld defects including surface and subsurface defects were subjected to magneto-optical imaging (MOI) nondestructive testing (NDT) experiments. The MO images of different weld defects under alternating magnetic field excitation and rotating magnetic field excitation have been compared to determine the best effect of nondestructive testing, and a cruciform welding seam was used to verify the detection effect of rotating magnetic field. Besides, the values of standard deviation and maximum difference have been determined to analyze the difference in the effects of two magnetic fields, and image processing methods were applied to extract defect information, such as histogram equalization. Experimental results show that the optimal excitation voltage and lift-off value of rotating magnetic field are 120 V and 20 mm, respectively; image histogram equalization can significantly improve the contrast of MO images, and there is a distinct difference in the detection effect of two magnetic fields. Under the same excitation conditions, the detection effect of rotating magnetic fields is always better than the effect of alternating magnetic fields, and rotating magnetic field excitation has obvious advantages in detecting multidirection and subsurface defects in that the detection depth can reach about 8 mm.